The Influence of School Organizational Culture and Teacher Self-Efficacy on Work Ethic - Anisa Mega Nur Safitri; Diyah Rieka Rahmawati; Dwi Kurnianing Ratri (Faculty of Education Universitas Negeri Malang, 2021)
The objectives of this study: (1) describe the culture of school organization, teacher self-efficacy, and work ethic of state high school teachers in Pasuruan City; (2) describe the influence of school organizational culture, self-efficacy on work ethics, either partially or simultaneously; (3) knowing that there are differences in characteristics between SMA and SMK. The research method used is through a quantitative approach with descriptive data analysis and multiple linear regression. The results showed: school organizational culture, teacher’s self-efficacy, and teacher’s work ethic of state high school in Pasuruan City were fairly in a good categor.